Research progress on the development of new nano materials for solar-driven sorption-based atmospheric water harvesting and corresponding system applications - Liu, Qianwen; Qin, Caiyan; Solomin, Evgeny; Chen, Qiang; Wu, Wenjing; Zhu, Qunzhi; Mahian, Omid (Nano Energy)
Atmospheric water harvesting presents an effective solution to the global freshwater crisis by passively adsorbing and collecting water molecules from the air. Solar-driven sorption-based atmospheric water harvesting (SSAWH) is gaining attention due to its low energy consumption, distributable, and environmentally friendly freshwater production method. SSAWH can serve as a vital tool to alleviate water scarcity in remote and arid regions. This review deals with recent advancements in SSAWH technology research. The development and performance of traditional porous adsorbents, hygroscopic salts, hydrogels, MOFs, photothermal materials, and new bionic-type porous materials were compared to analyze their advantages and limitations when applied to SSAWH. We propose corresponding research and development ideas to address the issues. Furthermore, the design improvements of water collection systems and devices applied in real-life scenarios were reviewed and summarized. Lastly, this article provides an outlook on the future development of the field.